Thermoelectric performance of electrodeposited nanostructured polyaniline doped with sulfo-salicylic acid - Chatterjee, K. (2014)
Conducting polymers, in present days, are considered to be potential thermoelectric (TE) materials. Among them polyaniline (PANI) is a promising candidate. Nanostructured polyaniline doped with organic dopant is electrodeposited and structurally characterized. Its transport properties are investigated for thermoelectric applications. The analysis of transmission electron microscopy image reveals that the sample is rod like nanostructure. This study shows that the type (inorganic/organic) of dopants plays an important role to influence the dimension of nanostructure and the electrical transport properties of PANI. In this study, organic dopant sulfosalicylic acid is proposed for enhancement of figure of merit through an increase in thermoelectric power and decrease in thermal conductivity. Compared to our earlier work the figure of merit evaluated is two orders higher than that of the inorganic dopant bismuth nitrate doped PANI. Â© 2013 Wiley Periodicals, Inc.